Association of Estimated Glomerular Filtration Rate (eGFR) and High-Sensitivity C-Reactive Protein (Hs-CRP) with the Risk of New-Onset Atrial Fibrillation in Patients with Diabetes - Liu Y; Liu H; Sun D; Zheng Y; Tse G; Chen K; Qiu J; Wu S; Liu T (Journal of Inflammation Research)
Ying Liu,1,* Hongmin Liu,1,2,* Dongkun Sun,1,* Yi Zheng,1 Gary Tse,1,3,4 Kangyin Chen,1 Jiuchun Qiu,1 Shouling Wu,2 Tong Liu1 1Tianjin Key Laboratory of Ionic-Molecular Function of Cardiovascular Disease, Department of Cardiology, Tianjin Institute of Cardiology, The Second Hospital of Tianjin Medical University, Tianjin, 300211, People’s Republic of China; 2Department of Cardiology, Kailuan General Hospital, Tangshan, 063001, People’s Republic of China; 3School of Nursing and Health Sciences, Hong Kong Metropolitan University, Hong Kong, People’s Republic of China; 4Diabetes Research Unit, Cardiovascular Analytics Group, PowerHealth Research Institute, Hong Kong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Tong Liu, Tianjin Key Laboratory of Ionic-Molecular Function of Cardiovascular disease, Department of Cardiology, Tianjin Institute of Cardiology, The Second Hospital of Tianjin Medical University, No. 23 Pingjiang Road, Hexi District, Tianjin, 300211, People’s Republic of China, Email liutong@tmu.edu.cn; liutongdoc@126.com Shouling Wu, Department of Cardiology, Kailuan General Hospital, Tangshan, 063001, People’s Republic of China, Email drwusl@163.comBackground: Both renal function decline and systemic inflammation may synergistically increase the risk of atrial fibrillation (AF). This study investigates the association between estimated glomerular filtration rate (eGFR) and high-sensitivity C-reactive protein (hs-CRP) levels with the risk of new-onset AF in patients with diabetes mellitus.Methods: We included diabetic patients without AF who participated in physical exams in the Kailuan Study from 2006 to 2010. Participants were categorized into four groups based on baseline eGFR and hs-CRP levels: 1) high eGFR (≥ 60 mL/min/1.73m²) and low hs-CRP (< 3 mg/L) (n=6,915), 2) high eGFR and high hs-CRP (≥ 3 mg/L) (n=3,154), 3) low eGFR (< 60 mL/min/1.73m²) and low hs-CRP (n=4,638), 4) low eGFR and high hs-CRP (n=1,809). We employed multivariable Cox regression analysis to evaluate the relationships between eGFR, hs-CRP, and new-onset AF, adjusting for confounders including smoking status, alcohol consumption, blood pressure, fasting blood glucose (FBG), heart rate, lipid levels, body mass index (BMI), and medication usage. Competing risk analysis was also performed.Results: Among 16,516 patients, 222 developed new-onset AF over a mean follow-up of 12.6 years. After adjusting for confounders, elevated hs-CRP and reduced eGFR were significantly associated with higher risk of new-onset AF compared to the high eGFR/low hs-CRP group. These findings remained consistent after excluding AF cases within the first 2-year. No significant interaction between eGFR and hs-CRP was observed (P=0.227). Subgroup analysis revealed that the combination of eGFR and hs-CRP had predictive value primarily in males under 60 years of age, individuals with FBG < 9 mmol/L, hypertension, and those not on hypoglycemic medications.Conclusion: In diabetic patients, decreased eGFR and elevated hs-CRP were independently linked to an increased risk of new-onset AF, emphasizing the importance of monitoring these factors for early detection and prevention of AF.Keywords: estimated glomerular filtration rate, high-sensitivity C-reactive protein, atrial fibrillation, diabetes mellitus